Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Melalui Kompetensi terhadap Kinerja Dosen di Universitas Graha Karya Batang Hari - Hendra Kurniawan; Fakhrul Rozi Yamali; Evi Adriani; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
The research objective is to determine the influence of leadership style and work environment through competence on lecturer performance. This research uses descriptive verification analysis. Data analysis was carried out using Path analysis and partial hypothesis testing with the help of the IBM SPSS Version 22 program. The results of the Path analysis showed a total effect of 27.27%. The results of the partial t test for leadership style and competency variables H0 are rejected, meaning that they have a significant influence on performance variables. Meanwhile, the work environment variable H1 is rejected, meaning that it does not have a significant effect on performance variables.